Investigating Intracellular Localisation and Cytotoxicity Trends for Neutral and Cationic Iridium Tetrazolato Complexes in Live Cells - Caporale, C.; Bader, C.; Sorvina, A.; Magee, K.; Skelton, B.; Gillam, T.; Wright, P.; Raiteri, Paolo; Stagni, S.; Morrison, J.; Plush, S.; Brooks, D.; et al. (Wiley, 2017)
A family of five neutral cyclometalated iridium(III) tetrazolato complexes and their methylated cationic analogues have been synthesised and characterised. The complexes are distinguished by variations of the substituents or degree of p conjugation on either the phenylpyridine or tetrazolato ligands. The photophysical properties of these species have been evaluated in organic and aqueous media, revealing predominantly a solvatochromic emission originating from mixed metal-to-ligand and ligand-to-ligand charge transfer excited states of triplet multiplicity. These emissions are characterised by typically long excited-state lifetimes (~hundreds of ns), and quantum yields around 5-10% in aqueous media. Methylation of the complexes caused a systematic red-shift of the emission profiles. The behaviour and the effects of the different complexes were then examined in cells. The neutral species localised mostly in the endoplasmic reticulum and lipid droplets, whereas the majority of the cationic complexes localised in the mitochondria. The amount of complexes found within cells does not depend on lipophilicity, which potentially suggests diverse uptake mechanisms. Methylated analogues were found to be more cytotoxic compared to the neutral species, a behaviour that might to be linked to a combination of uptake and intracellular localisation.